Some Regularities in Establishing Regional Categories of Specially Protected Natural Territories - Syomin, Pavel (Journal of Economic Sociology, 2020)
Protection of the environment and specially protected natural territories are in the joint jurisdiction of the Russian Federation and its constituent entities. In particular, constituent entities have the power to establish their own categories of specially protected natural territories (called regional categories) besides the categories prescribed by the federal law On Specially Protected Natural Territories. The diversity of regional categories has been studied only superficially, despite the fact that such research may be valuable for finding out the drawbacks of federal and regional legislation and for identifying the ways it can be improved. It may also result in general insights about Russian lawmaking under joint jurisdiction. The study presented in this paper aimed to find the regularities in the legislative activity of Russia’s constituent entities in the field of establishing regional categories. For this purpose, the full list of regional categories as of August 1, 2019 was made and then processed with text mining algorithms, including word clouds, bigram analysis, word correlations, and clustering of categories’ names using their vector representations made with Fasttext. Several large groups of regional categories were determined as a result: protected natural objects (analogous to natural monuments), protected landscapes and natural complexes, protected green zones of populated localities, recreational areas, and areas of historical and cultural designation, which are similar to cultural heritage objects. Some constituent entities fill the gaps in federal regulation; they follow the paradigm of anticipatory lawmaking and provide for special rules for territories under international agreements, such as wetlands of international importance, or they partially implement protected area categories adopted by the International Union for Conservation of Nature. However, some regional categories are likely to indicate a low level of legal technique in regional lawmaking. This analysis of regional categories points out three deficiencies of the Russian federal legislation on protected areas: instability of legislation, excessive rigidity of the federal categories system, and flaws in the protection of areas valuable for conservation of biodiversity, recreation, and support for ecological balance.